Functional Evaluation of the Reusable JuniorSTAR® Half-Unit Insulin Pen. (28th January 2015) - Klonoff, David; Nayberg, Irina; Rabbone, Ivana; Domenger, Catherine; Stauder, Udo; Oualali, Hamid; Danne, Thomas
Background: The functional performance of the JuniorSTAR ® (Sanofi, Paris, France) half-unit insulin pen was evaluated through a series of specific objective tests to assess the dose accuracy, pen weight, injection force, and dialing torque.Method: Pens (n = 60) were tested under standard atmospheric conditions with 3 different types of insulins manufactured by Sanofi (insulin glargine, insulin glulisine, and biphasic insulin isophane). The dose accuracy was tested according to the ISO 11608-1:2012 standards. Injection doses of 0.010, 0.155, and 0.300 ml were evaluated. For mean weight evaluation, the pens without the cartridge were weighed on precision balances. The injection force was measured using a texture analyzer and the dialing torque was measured using a torque meter.Results: JuniorSTAR met the ISO 11608-1:2012 criteria for dose accuracy as all the delivered doses were within the predefined limits for all types of insulin tested. The mean weight of the JuniorSTAR pen was 33.4 g (SD = 0.075). The mean injection force was 6.0 N (SD = 0.8), 4.3 N (SD = 0.4), and 5.1 N (SD = 0.6) for insulin glargine, insulin glulisine, and biphasic insulin isophane, respectively. The mean dialing torque was 5.09 Ncm (SD = 0.29) and 5.88 Ncm (SD = 0.53) for setting and correcting a dose, respectively.Conclusions: Together with results from a previously reported usability survey, these results show that the JuniorSTAR reusable, half-unit pen is a lightweight and accurate device for insulin delivery with a dialing torque and injection force suitable for young people with type 1 diabetes.